2017
DOI: 10.3389/fmicb.2017.00535
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-helminthic Compound Mebendazole Has Multiple Antifungal Effects against Cryptococcus neoformans

Abstract: Cryptococcus neoformans is the most lethal pathogen of the central nervous system. The gold standard treatment of cryptococcosis, a combination of amphotericin B with 5-fluorocytosine, involves broad toxicity, high costs, low efficacy, and limited worldwide availability. Although the need for new antifungals is clear, drug research and development (R&D) is costly and time-consuming. Thus, drug repurposing is an alternative to R&D and to the currently available tools for treating fungal diseases. Here we screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 62 publications
5
78
0
4
Order By: Relevance
“…We asked whether the mechanism of anti-cryptococcal activity of fenbendazole was similar to what was previously described for C. gattii (16) or if it was related to its well characterized anthelmintic effect (1921). Mutant strains of C. gattii lacking expression of the Aim25 scramblase or the nucleolar protein Nop16 were resistant to mebendazole (16), suggesting that these proteins are potential targets for the antifungal activity of benzimidazoles. To investigate the mechanism of action of fenbendazole, we first evaluated its antifungal activity against mutant strains of C. gattii lacking the AIM25 or NOP16 genes and observed that both strains and wild type cells were similarly sensitive to this benzimidazole (Figures 2A and B).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…We asked whether the mechanism of anti-cryptococcal activity of fenbendazole was similar to what was previously described for C. gattii (16) or if it was related to its well characterized anthelmintic effect (1921). Mutant strains of C. gattii lacking expression of the Aim25 scramblase or the nucleolar protein Nop16 were resistant to mebendazole (16), suggesting that these proteins are potential targets for the antifungal activity of benzimidazoles. To investigate the mechanism of action of fenbendazole, we first evaluated its antifungal activity against mutant strains of C. gattii lacking the AIM25 or NOP16 genes and observed that both strains and wild type cells were similarly sensitive to this benzimidazole (Figures 2A and B).…”
Section: Resultsmentioning
confidence: 83%
“…The in vitro anti-cryptococcal activity of benzimidazoles has been consistently reported (1316). A general analysis of these reports on the anti-cryptococcal activity of benzimidazoles indicated that, among all members of this drug family, fenbendazole required the lowest MIC against C. neoformans and C. gattii , in comparison to other benzimidazoles (1316). In addition, a detailed study on the toxicity of fenbendazole suggested high levels of safety in humans (17, 18).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations